Relevansi Kegiatan Muhadharah dengan Kemampuan Public Speaking Peserta Didik di Man 1 Kampar - Sukmawati; Nadhila Mastura; Risnawati; Miftahir Rizqa (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research aims to determine the relevance of Muhadharah activities to the public speaking ability of students at MAN 1 Kampar. This type of research is correlational research using a quantitative approach. The population in this study was 75 people using total sampling data collection techniques, i.e., making the entire population the sample. The data collection techniques are observation, documentation, and questionnaires. The data analysis technique uses the product-moment correlation test. The results obtained in this research are rcount 0.647 > rtable at the 5% significance level (0.227), and at the 1% significance level (0.296), it can be concluded that Ha is accepted and H0 is rejected. Thus, there is a positive relevance of muhadharah activities to the public speaking skills of students at MAN 1 Kampar. The contribution of muhadharah activities to the public speaking skills of students in this study was 41.9%, while 58.1% was influenced or explained by other variables.